INTEGRATION OF ARTIFICIAL INTELLIGENCE AND MOBILE LEARNING IN ISTIMĀ‘ INSTRUCTION AT MTS DARUL FIKRI - Fitrah, Aditya; Paujiyah, Nadatul; Kosim, Abdul; Karim, Agus; Ali Firdaus, Muhammad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Arabic language learning still faces challenges in the form of low motivation and limited innovative media. This problem is evident in listening skills, which require modern technological support to be developed effectively. The emergence of Artificial Intelligence (AI) and mobile learning offers solutions through adaptive and interactive learning experiences in line with the Society 5.0 era. This study aims to provide education on the application of AI and mobile learning in learning, train teachers and students to be able to use technology effectively in listening learning, and improve the listening skills of students in madrasas. Using a Participatory Action Research (PAR) approach, this study involved teachers, students, and foundations at every stage. Data was collected through interviews, observations, satisfaction questionnaires, and pre-tests and post-tests, followed by qualitative and quantitative analysis. The results show that the integration of AI and mobile learning in istimā‘ teaching positively improves the quality of Arabic language learning. This is reflected in the satisfaction levels of seminar participants (92.5%) and students (96.9%), indicating that technology-based approaches create a more engaging and accessible learning environment. AI also supports teachers in designing materials more efficiently while providing exercises tailored to students' needs. However, challenges remain, such as limited device availability, unstable internet access, and low digital literacy among teachers, which hinder optimal implementation.